2020
DOI: 10.1016/j.enbuild.2019.109703
|View full text |Cite
|
Sign up to set email alerts
|

System-level key performance indicators for building performance evaluation

Abstract: Quantifying building energy performance through the development and use of key performance indicators (KPIs) is an essential step in achieving energy saving goals in both new and existing buildings. Current methods used to evaluate improvements, however, are not well represented at the system-level (e.g., lighting, plug-loads, HVAC, service water heating). Instead, they are typically only either measured at the whole building level (e.g., energy use intensity) or at the equipment level (e.g., chiller efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
(22 reference statements)
0
25
0
Order By: Relevance
“…Building energy performance has typically been evaluated at a whole-building level (energy use intensity, peak demand) or at equipment level (e.g., chiller efficiency coefficient of performance (COP)) [10]. Whole building metrics like energy use intensity (EUI), peak demand, and thermal energy demand intensity (TEDI) represent whole building performance normalized by floor area, where EUI is the whole building energy use normalized by floor area and TEDI is the space heating and ventilation output normalized by floor area [11].…”
Section: Overview Of Whole Building and System Performance Metricsmentioning
confidence: 99%
“…Building energy performance has typically been evaluated at a whole-building level (energy use intensity, peak demand) or at equipment level (e.g., chiller efficiency coefficient of performance (COP)) [10]. Whole building metrics like energy use intensity (EUI), peak demand, and thermal energy demand intensity (TEDI) represent whole building performance normalized by floor area, where EUI is the whole building energy use normalized by floor area and TEDI is the space heating and ventilation output normalized by floor area [11].…”
Section: Overview Of Whole Building and System Performance Metricsmentioning
confidence: 99%
“…Feiz et al (2020) demonstrated the economic and environmental KPIs of the renewable energy production system by adopting a life cycle assessment (LCA) approach and ignored to examine the significance of proposed KPIs. Li, Hong, Lee, and Sofos (2020) proposed system‐level KPIs for building performance evaluation using a simulation based approach, and the study findings were not suitable for the manufacturing industries. Zhu et al (2018) identified the KPIs for the process industries, which were neglected by the KPIs series of ISO 22400.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These KPI studies can help support energy management decision making and investment [28,29]. To facilitate comparisons among sites, a normalized energy use KPI can be helpful, such as the energy use per patient bed [30].…”
Section: Introductionmentioning
confidence: 99%